English: Bahasa Indonesia - Lestari, Shyntiya Ayu; Putri, Dian Kemala (Universitas Katolik Parahyangan, 2024)
The concentration of studies is very important to support students in understanding the theory and understanding the concepts during learning activities so this needs to be noted so that students can achieve good learning outcomes. Studying while working will certainly cause serious problems to the process of activities on campus and at work. Problems that often occur are piling up tasks, difficulty managing time, fatigue, disputes between colleagues and superiors, a toxic work environment, limited rest time, being expelled from university, and experiencing a delay in graduation. These can trigger job stress for students because they have to do two activities in their daily lives. This study aims to find out the effect of job stress levels on study concentration in working students. In addition, this study analyzes the factors that influence job stress and study concentration. The method used is quantitative analysis with a non-probability sampling technique with a purposive sampling technique. The analysis of data carried out was a Chi-Square test and t-test. Based on the results shows that students who study while working have a very high level of job stress which causes a decrease in learning concentration in students. In addition, several factors influence job stress and study concentration, namely gender, age, type of work, and length of work duration. This research contributes to providing an overview and consideration to students about students who study while working.